INVESTIGASI FAKTOR-FAKTOR YANG MEMPENGARUHI PARTISIPASI DISKUSI ONLINE: STUDI KASUS STUDENT-CENTERED E-LEARNING ENVIRONMENT MAGISTER TEKNOLOGI INFORMASI UNIVERSITAS INDONESIA - Meyer Sihotang; Widijanto Satyo Nugroho (Faculty of Computer Science Universitas Indonesia, 2015)
The use of e–Learning in Universitas Indonesia has been regulated by The Official Decree of The Rector of the Universitas Indonesia. Data derived from the log activity of SCeLE Admin shows that the discussion forum within SCeLE, from the year 2011 to 2014, has not been utilized optimally by both students and lecturers. This is shown by a number of discussion forums and topics that were below 15 percent. The objective of this research is to investigate the factors that influence participation of online discussions within SCeLE MTI Universitas Indonesia (UI). Data is collected using questionnaires that are given to 150 students of MTI Study Program UI. Data processing used partial least square–SEM (PLS-SEM) with the aid of smartPLS3 software. Research finding shows that several factors that influence SCeLE online discussion generally are extrinsic motivation, habit, information quality, performance expectancy, social influence, system quality, and service quality. The factors that are very influential to behavioral intention are performance expectancy, habit, extrinsic motivation and social influence. Meanwhile, the factors that are very influential to user satisfaction are information quality, system quality and service quality.